PENGARUH METODE INQUIRI TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIK SISWA SMAN 1 MANDE KABUPATEN CIANJUR - ABDUL JALALUDIN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2021)
This research is an experimental study that focuses on increasing the mathematical creative thinking skills of high school students by applying the inquiry learning method. The problem behind this research is the lack of familiarity with learning using methods with a focus on learning on students as a way to get a more meaningful learning experience based on students' creative thinking skills that are different for each student. The aims of this study are: 1) To determine the effect of the inquiry learning method on students' mathematical creative thinking skills. 2) to find out the comparison of increasing students' mathematical creative thinking skills using the inquiry learning method with conventional learning; 3) to determine students' attitudes towards learning the inquiry method. This study used the experimental design method